Dose‐dependent effects of alpha‐naphthylisothiocyanate disconnect biliary fibrosis from hepatocellular necrosis. Issue 1 (8th September 2016) - Joshi, Nikita; Ray, Jessica L.; Kopec, Anna K.; Luyendyk, James P.
Abstract: Exposure of rodents to the xenobiotic α‐naphthylisothiocyanate (ANIT) is an established model of experimental intrahepatic bile duct injury. Administration of ANIT to mice causes neutrophil‐mediated hepatocellular necrosis. Prolonged exposure of mice to ANIT also produces bile duct hyperplasia and liver fibrosis. However, the mechanistic connection between ANIT‐induced hepatocellular necrosis and bile duct hyperplasia and fibrosis is not well characterized. We examined impact of two different doses of ANIT, by feeding chow containing ANIT (0.05%, 0.1%), on the severity of various liver pathologies in a model of chronic ANIT exposure. ANIT‐elicited increases in liver inflammation and hepatocellular necrosis increased with dose. Remarkably, there was no connection between increased hepatocellular necrosis and bile duct hyperplasia and peribiliary fibrosis, as these pathologies increased similarly in mice exposed to either dose of ANIT. The results indicate that the severity of hepatocellular necrosis does not dictate the extent of bile duct hyperplasia/fibrosis in ANIT‐exposed mice.